PENEGAKAN HUKUM TERHADAP ALIH FUNGSI LAHAN PERTANIAN MENJADI LAHAN NON PERTANIAN: (Studi Kasus Terkait Alih Fungsi Lahan Di Kawasan Jl. Semeru, Kel. Wates, Kec. Magersari, Kota Mojokerto) - Indika, Dina; Widodo, Hananto (NOVUM : JURNAL HUKUM, 2019)
Abstract The problem of the large number of conversions of agricultural land that is increasingly spreading until now has the potential to erode the availability of agricultural land which is used as a livelihood for farmers to maintain food security or also known as food self-sufficiency. Seeing that there are still many problems in the conversion of agricultural land into non-agricultural land into trade and service areas, questioning the existence in the enforcement of Law no. 26 of 2007 concerning Spatial Planning and Mojokero City Regional Regulation Number 4 of 2012 concerning Mojokerto City Spatial Planning for 2012-2032 The number of conversions of agricultural land continues to increase from time to time. This does not rule out the possibility of additional cases of transfer of function every year which have an impact on the sustainability of food self-sufficiency, reduced livelihoods of farmers, and reduced agricultural land. To stem the land conversion, it is necessary to be firm in law enforcement against the conversion of agricultural land to non-agricultural land (a case study related to land conversion in the area of ??Jl. Semeru, Kel. Wates, Kec. Magersari, Mojokerto City) in order to anticipate the transfer of land. land functions that are not in accordance with established regulations. Keywords: Agricultural land conversion, Law no. 26 of 2007, Law enforcement